A review: partial discharge in medium voltage cross-linked polyethylene XLPE cable - Bahari N.S.B.A.; Mei K.T.; Ariffin A.B.M. (Institute of Physics, 2024)
Power cables are one of the equipment that plays a vital role in the power system network, either in High Voltage (HV) or Medium Voltage (MV) network. To ensure a reliable power supply and distribution, the integrity and the condition of the cable system must be ensured. Partial Discharge (PD) diagnosis is a valuable tool to analyse and evaluate the condition of the insulation. The purpose of this paper is to review how PD activity is being utilized to assess the condition of the XLPE (cross-linked polyethylene) cables specifically in MV level where a review of existing PD test methodology that are used by researchers and engineers to diagnose the insulation condition of the cable will be presented. 2023 Institute of Physics Publishing. All rights reserved.